TraveLux: An Interaction-based Brand Relationship Scale for the Luxury Travelers - BAKSI, ARUP KUMAR (Turizam, 2021)
Luxury consumption is on the rise over the last two decades. This brings challenge for the luxury brand marketers to sustain with the aspirational quotient of the luxury consumers. The inherent perception associated with the luxury consumption, namely narrow-band of consumers having ability to pay premium price, has given way to mass luxury consumption, thereby diminishing the price sensitivity of the segment. This luxury paradox calls for a fresh look into the equations that influence and control the relationship between the consumers and luxury brands. This study aims to develop a brand relationship instrument, namely, TraveLux, with specific reference to the travel, tourism and hospitality industry. The cross-sectional study was conducted in three major tourism destinations of India, namely, Rajasthan, Kerala and Goa. The initial scale items for the instrument were obtained by collating past studies and conducting a focus group exercise. The instrument was empirically tested to identify the relationship factors. Findings revealed that the TraveLux Brand Relationship can be mounted on four factors (dimensions), namely, immersive experience, ethno-cultural acculturation, passion & excitement and self congruence. The validated scale was further tested for possible deviations with new group of respondents. The measurement invariance did not reveal significant difference between the baseline model and the tested model. TraveLux will provide a framework for the luxury-travel brand marketers to develop specific brand designs and brand communications based on the identified relationship factors. Future research may be conducted to expand the scope of the instrument to embed behavioural and attitudinal issues of the travelers.